The use of anthracycline at first‐line compared to alkylating agents or nucleoside analogs improves the outcome of salvage treatments after relapse in follicular lymphoma The REFOLL study by the Fondazione Italiana Linfomi. Issue 1 (19th November 2014) - Rossi, Giuseppe; Marcheselli, Luigi; Dondi, Alessandra; Bottelli, Chiara; Tucci, Alessandra; Luminari, Stefano; Arcaini, Luca; Merli, Michele; Pulsoni, Alessandro; Boccomini, Carola; Puccini, Benedetta; Micheletti, Moira; et al.
<x xml:space="preserve">Abstract</x> Follicular lymphoma (FL) patients experience multiple remissions and relapses and commonly receive multiple treatment lines. A crucial question is whether anthracyclines should be used at first‐line or whether they would be better "reserved" for relapse and whether FL outcome can be optimized by definite sequences of treatments. Randomized trials can be hardly designed to address this question. In this retrospective multi‐institutional study, time‐to‐next‐treatment after first relapse was analyzed in 510 patients who had received either alkylating agents‐ or anthracycline‐ or nucleoside analogs‐based chemotherapy with/without rituximab at first‐line and different second‐line therapies. After a median of 42 months, median time‐to‐next‐treatment after relapse was 41 months (CI95%:34–47 months). After adjustment for covariates, first‐line anthracycline‐based chemotherapy with/without rituximab was associated with better time‐to‐next‐treatment after any salvage than alkylating agents‐based chemotherapy with/without rituximab or nucleoside analogs‐based chemotherapy with/without rituximab (HR:0.74, P = 0.027). The addition of rituximab to first‐line chemotherapy had no significant impact (HR:1.22, P = 0.140). Autologs stem cell transplantation performed better than any other salvage treatment (HR:0.53, P < 0.001). First‐line anthracycline‐based chemotherapy significantly improved time‐to‐next‐treatment even in patients receiving salvage autologs stem cell transplantation (P = 0.041). This study supports the concept that in FL previous treatments significantly impact on the outcome of subsequent therapies. The outcome of second‐line treatments, either with salvage chemoimmunotherapy or with autologs stem cell transplantation, was better when an anthracycline‐containing regimen was used at first‐line. Am. J. Hematol. 90:56–61, 2015. © 2014 Wiley Periodicals, Inc.